Commuting to the Reykjavík capital area from Southwest Iceland - Bjarnason, Þóroddur; Þórðardóttir, Sigríður Elín (Research in applied business and economics, 2018)
In recent years regions within commuting distance from the Reykjavík urban area have grown faster than the capital area as such. In this study, commuting to the capital area is compared to work within the home community and commuting within each region. Special attention is given to the effects of gender, age, education and employment sector on commuting to the capital area from different areas. The research is based on data on commuting to the capital area from different parts of Iceland collected by Gallup for the Icelandic Regional Development Institute in a mixed internet and phone survey in 2017. The results show that commuting to the capital area is an important part of the job markets in the southwest region, in particular in the area from Vogar á Vatnsleysuströnd to Akranes, Þorlákshöfn and Hveragerði. Commuting to the capital area is more important for men than women and university education is associated with more commuting to the capital area among younger respondents. The level of commuting is highest in the sectors of science and technology, administration, associations and cultural activities but lowest in primary production and education. With the exception of Vogar, however, commuting to the capital area is far from being the most important source of employment for residents of the southwest region. More people work in their home community than in the capital area and in most regions more people commute to other communities within the region than to the capital area. Á undanförnum árum hafa landsbyggðir í seilingarfjarlægð frá borgarsvæði Reykjavíkur vaxið talsvert hraðar en höfuðborgarsvæðið sem slíkt. Í þessari rannsókn er vinnusókn til höfuðborgarsvæðisins metin í samanburði við vinnusókn innan heimabyggðar og til annarra byggðarlaga í viðkomandi landshluta. Sérstaklega verður litið til áhrifa kyns, aldurs, menntunar og tegundar starfs á vinnusókn til höfuðborgarsvæðisins eftir byggðarlögum. Rannsóknin byggir á gögnum um vinnusókn frá einstökum landshlutum til höfuðborgarsvæðisins sem Gallup ...